Switchable Nitroproteome States of Phytophthora infestans Biology and Pathobiology - Izbiańska, Karolina; Floryszak-Wieczorek, Jolanta; Gajewska, Joanna; Gzyl, Jarosław; Jelonek, Tomasz; Arasimowicz-Jelonek, Magdalena (Frontiers in Microbiology, 2019)
The study demonstrates protein tyrosine nitration as a functional posttranslational modification in biology and pathobiology of the oomycete Phytophthora infestans (Mont.) de Bary, the most harmful pathogen of potato (Solanum tuberosum L.). Using two P. infestans isolates differing in their virulence towards potato cv. Sarpo Mira we found that the pathogen generates reactive nitrogen species (RNS) in hyphae and mature sporangia growing under in vitro and in planta conditions. However, acceleration of peroxynitrite formation and elevation of the nitrated protein pool within pathogen structures were observed mainly during the avr P. infestans MP946-potato interaction. Importantly, the nitroproteome profiles varied for the pathogen virulence pattern and comparative analysis revealed that vr MP 977 P. infestans represented a much more diverse quality spectrum of nitrated proteins. Abundance profiles of nitrated proteins that were up- or downregulated were substantially different also between the analyzed growth phases. Briefly, in planta growth of avr and vr P. infestans was accompanied by exclusive nitration of proteins involved in energy metabolism, signal transduction and pathogenesis. Importantly, the P. infestans-potato interaction indicated cytosolic RXLRs and Crinklers effectors as potential sensors of RNS. Taken together, we explored the first plant pathogen nitroproteome. The results present new insights into RNS metabolism in P.infestans indicating protein nitration as an integral part of pathogen biology, dynamically modified during its offensive strategy. Thus, the nitroproteome should be considered as a flexible element of the oomycete developmental and adaptive mechanism to different micro-environments, including host cells.